"Better everyone should know our business than we lose our house": Costs and benefits of medical crowdfunding for support, privacy, and identity. (February 2018) - Gonzales, Amy L; Kwon, Elizabeth Y; Lynch, Teresa; Fritz, Nicole
In the United States, medical crowdfunding is an increasingly common response to overwhelming healthcare costs. Semi-structured interviews were conducted with 30 individuals crowdfunding for health (e.g. cancer, paralysis, brain injury) on behalf of themselves or others, to better understand this new phenomenon as it informs theory on social support, identity, and privacy. First, findings suggest that crowdfunding is often a resource for both instrumental and emotional social support. Second, many crowdfunders weighed the need for support against perceived privacy risks, which is consistent with and extends privacy calculus theory . Finally, highly vulnerable self-disclosures were often reinterpreted to be empowering, which also supports and extends work on identity shift . Using crowdfunding as a context for inquiry, findings point to new theoretical frameworks to describe how users navigate needs for both privacy and support online and the often positive consequences of that negotiation for identity.